The neuropeptide Y single-nucleotide polymorphism rs16147:T>C moderates the effect of alcohol dependence on depression in male Chinese Han population - Wei, Xiaojie; Cai, Fangfang; Zhou, Siyao; Zhang, Jinjing; Xu, Kewei; Shen, Guanghui; Sun, Huankun; Yang, Fan; Hong, Liuzhi; Zou, Yang; Chen, Yu-Hsin; Liu, Yanlong; et al. (Frontiers in Psychiatry, 2022)
Background: Previous studies suggest that alcohol dependence is associated with depression, however, the effect of alcohol dependence varies from individual to individual, which may be due to different genetic backgrounds. The interactions between alcohol dependence and different gene polymorphisms may finally shape the onset of depression. Neuropeptide Y (NPY), which can maintain homeostasis from high-stress stimulation, may protect individuals from the onset of depression. Here, we explored whether the NPY rs16147:T>C has an association with depression in individuals with alcohol dependence during the period of alcohol dependence withdrawal. Methods: A total of 455 males with alcohol dependence were recruited. The scale of Michigan Alcoholism Screening Test (MAST) and Self-Depression Scale (SDS) were respectively used to analyze the condition of alcohol dependence and depression. Genomic DNA was extracted from each blood sample and NPY polymorphisms were genotyped. The interaction between NPY rs16147:T>C and alcohol dependence on depression was first analyzed. Then, region of significance analysis was used to confirm which model provided the best fit for the interaction (diathesis-stress or differential susceptibility). Finally, by using internal replication analyses, the accuracy and robustness of the interaction results were improved. Results: Alcohol dependence was positively correlated with depression. CC homozygotes of NPYrs16147:T>C exhibited less depression when exposed to low alcohol dependence, but more depression when exposed to high alcohol dependence. Individuals with the T allele showed the opposite result. Conclusions: NPY rs16147:T>C might be correlated with susceptibility for depression in males during alcohol dependence withdrawal. The findings support the differential susceptibility model.